Higher Status Honesty Is Worth More: The Effect of Social Status on Honesty Evaluation - Blue, Philip R.; Hu, Jie; Zhou, Xiaolin (Frontiers in Psychology, 2018)
Promises are crucial for maintaining trust in social hierarchies. It is well known that not all promises are kept; yet the effect of social status on responses to promises being kept or broken is far from understood, as are the neural processes underlying this effect. Here we manipulated participants' social status before measuring their investment behavior as Investor in iterated Trust Game (TG). Participants decided how much to invest in their partners, who acted as Trustees in TG, after being informed that their partners of higher or lower social status either promised to return half of the multiplied sum (4 x invested amount), did not promise, or had no opportunity to promise. Event-related potentials (ERPs) were recorded when the participants saw the Trustees' decisions in which the partners always returned half of the time, regardless of the experimental conditions. Trustee decisions to return or not after promising to do so were defined as honesty and dishonesty, respectively. Behaviorally, participants invested more when Trustees promised than when Trustees had no opportunity to promise, and this effect was greater for higher status than lower status Trustees. Neurally, when viewing Trustees' return decisions, participants' medial frontal negativity (MFN) responses (250-310ms post onset) were more negative when Trustees did not return than when they did return, suggesting that not returning was an expectancy violation. P300 responses were only sensitive to higher status return feedback, and were more positive-going for higher status partner returns than for lower status partner returns, suggesting that higher status returns may have been more rewarding/motivationally significant. Importantly, only participants in low subjective socioeconomic status (SES) evidenced an increased P300 effect for higher status than lower status honesty (honesty - dishonesty), suggesting that higher status honesty was especially rewarding/motivationally significant for participants with low SES. Taken together, our results suggest that in an earlier time window, MFN encodes return valence, regardless of honesty or social status, which are addressed in a later cognitive appraisal process (P300). Our findings suggest that social status influences honesty perception at both a behavioral and neural level, and that subjective socioeconomic status may modulate this effect.